Ultrastructural findings of bone marrow in a case with malignant osteopetrosis following successful allogeneic bone marrow transplantation - Korkusuz, Petek; Aşan, Esin; Çetin, Mualla; Tuncer, Murat; Tezcan, İlhan (The Turkish Journal of Pediatrics, 1999)
A nine-month-old female patient suffering from malignant osteopetrosis was evaluated by light and transmission electron microscopic study before and following allogeneic bone marrow transplantation (BMT). Bone marrow specimens were obtained from iliac crest biopsies. Before BMT, the bone marrow had an irregular appearance and was filled with bridging bony trabeculae devoid of cells. Following BMT, the marrow had an almost normal appearance with no myelofibrosis and a relatively regular distribution of hematopoietic cells. The osteocytes were visible in their lacunae in the bone matrix. Presence of bone resorbing and bone forming cell together demonstrated that the bone was beginning to gain its normal dynamic structure. These findings were in accordance with the clinical, laboratory and radiological data which showed the beneficial effect of the therapy.
Keywords: malignant-infantile osteopetrosis; allogeneic bone marrow transplantation; ultrastructure